PERFORMANCE EVALUATION OF A MINI PERMANENT MAGNET SYNCHRONOUS GENERATOR (PMSG) FOR WIND ENERGY SYSTEM - TIMOTHY AIKA; SAMUEL IGBINOVIA; PATIENCE ORUKPE (Journal of Engineering Studies and Research)
In this work, the performance of a 500 W permanent magnet synchronous generator was evaluated in MATLAB /Simulink. The Simulink model consists of a wind turbine, a PMSG, and an AC – DC rectifier. The PMSG input parameter were measured and inputted in the Simulink block while the output results were voltages, currents and power respectively. The PMSG was tested at various wind speed. At the rated wind speed of 11m/s, the output power was 443.2 W.